Are lakes a public good or exclusive resource? Towards value-based management for aquatic invasive species. Issue 139 (January 2023) - McCumber, Andrew; Sullivan, Abigail; Houser, Matthew K.; Muthukrishnan, Ranjan
Abstract: Invasive species are a prominent driver of global environmental change and management of biological invasions is a complex issue that requires attention to social and ecological contexts. Management efforts implemented without consideration of social dimensions have often been delayed or have failed due to community resistance. Despite this, much invasive species research has focused solely on the ecological dynamics of invasions. To advance our understanding of the social dimensions of efforts to confront invasive species, we analyze decision-making among stakeholders impacted by starry stonewort ( Nitellopsis obtusa ), a freshwater alga and key emerging invader in lakes in the upper midwestern US that, to our knowledge, has not been explored in the human dimensions of invasive species literature. Through a content analysis of 46 semi-structured interviews with stakeholders associated with lakes invaded by N. obtusa in Indiana, Wisconsin, and Minnesota, we assess stakeholders' management preferences and the factors that shape both preferences and current practices. We examine current management strategies, perceptions of the importance of addressing starry stonewort, and stakeholder goals, as well as motivational and structural factors that shape and potentially limit decision-making. We highlight two "lake ethics" that emerge from our results where stakeholders see lakes as either a public good or an exclusive resource. We present a typology of these two distinct lake ethics and explore their implications for future efforts to manage N. obtusa, suggesting that managers should move towards value-based approaches that consider underlying community values tied to natural resources. Highlights: Starry stonewort ( Nitellopsis obtusa ) is a freshwater alga and key emerging invader. We present the first qualitative study of N. obtusa stakeholders. Two "lake ethics" emerge where stakeholders see management distinctly. Stakeholders fall under the "public good" or "exclusive resource" ethic. We present a typology for helping managers move towards value-based approaches.